STUDI EVALUASI TENTANG EFEKTIVITAS IMPLEMENTASI PROGRAM PEMERATAAN PENDIDIKAN DASAR MELALUI PROGRAM PEMBERIAN EASISWA RETRIVAL KEPADA SISWA RAWAN DROP OUT (DO) TERUTAMA MISKIN DAN PEREMPUAN (STUDI DI KABUPATEN LOMBOK TIMUR) - Muhammad Ali Gunawan (LPPM Universitas Pekalongan, 2010)
This study aimed at finding out the effectiveness of the implementation of the equal access to primary education program through the provision of retrieval scholarship to students with the high likelihood of dropping out, particularly, poor and female students, investigating its strength and weakness, the constrains encountered in its implementation. To achieve the goal, the data were collected from the Office of Education of East Lombok Regency and 16 (sixteen) primary education level schools (SD-MI and SMP-MTs) whose students got the retrieval scholarship in 2007, drawn by census. This study was an ex-post facto study. The data on the effectiveness of the implementation of this program of equal access to primary education through the provision of the retrieval scholarship, particularly, poor and female students were collected by questionnaire, interview guide and observation adopted from monitoring and evaluation guidelines of the project of Decentralized Basic Education ProjectAsian Development Bank (DBEP-ADB) of East Lombok Regency. The data were analyzed descriptive-quantitatively for the primary data collected by questionnaire, qualitative data (secondary) collected by interview, observation, and documentation were analyzed by qualitative analysis. From the results it was found: 1) The e ffect ive nes s o f imp le me nt at io n in t he o ff ice o f e ducat io n E a st Lo mbo k Rege nc y was ―ver y e ffect ive‖ w hile o ut o f t he 16 ( s ixt ee n) sc ho o ls t arget ed, 2(t wo) scho o ls wer e ―ver y e ffe ct ive ‖ cat ego r y, a nd 14 ( fo urt een) wer e ―e ffect ive ‖; 2) T he st r engt h o f t he pr o gr am: a) in he ig ht ened the level of awareness of the parents, teachers, and society of the importance of education; b) the procedure was easy and clear; c) there was a strong indication that the program reduced dropouts; d) there was a likelihood of reduction in subtracting the amount of scholarship or corruption; 3) The weaknesses included: a) to many members of the executing committee; b) the amount of scholarship provided or allocated could not meet the need, c) unfairness in its distribution, both among and within the schools, d) the likelihood of inter-program overlaps, e) a high tendency of deviation in the use of scholarship, f) the program did not sufficiently accommodate local contents, i.e. participative planning and use, g) the weakness of monitoring and control system at the lowest level although it has engaged the representatives o f t he so c iet y a nd st udent ’ s parents; 4) The constraints encountered were: a) the weakness of the data encoding and processing system, b) the low level professionalism of the program management in the office of education, c) the limitation of information and communication facilities in managing the program, d) the schools hesitated to collect data of the students with the high likelihood of dropping out, and e) the dropouts or the students with the high like liho o d ha ve wo r ked o ver sea s ( I ndo nes ia ’ s hu ma n po wer ) . E ffo r t co nduct ed to o v ercome the constraint is: a) organizer of program co-ordinate and data synchronization with related/relevant institutions, b) compile list of is division of duty (job description) clear and coherent, c) strive the existence of incentive to school, d) conduct important hitting campaign and socialization of education, e) there is no effort to overcome because reason of society economics which not yet stabilized.Key Words: Evaluative Study, Equal Access to Primary Education Program and Retrieval Scholarship Program, Dropouts, Poor and Female.